(untitled) (Contemporary Journal of Social Science Review, 2024)
This study was planned to test an empirical investigation of the mediating role of Resilience on the relationship between Entrepreneurs’ Improvisation and Innovation in small and medium enterprises of Pakistan. The purpose of this research was to analyze that whether Entrepreneur Improvisation impact innovation in SME’s of Pakistan. Data was collected by adopting clusters sampling technique of probability sampling design (based on area) from the managers/owners of small and medium size enterprises (SME’s), listed in Chambers of Commerce of Capital cities of Pakistan. This study is a part of extensive research and data was collected from 433 respondents with 73.33% response rate. Structural equation modeling (SEM) was used to test the hypotheses and path analysis. The results of the study showed that entrepreneurs’ improvisation has direct significant impact on innovation and resilience; and the resilience fully mediated the relationship between entrepreneurs’ improvisation and innovation which contributed in the existing body of knowledge as there is scant evidence in literature regarding full mediation of resilience on the relationship between entrepreneurs’ improvisation and innovation in context of SMEs. This research paper also suggested to the future researchers to test and analyze other mediators like adhocracy culture etc. in SMEs or large scale organizations.